Upaya Meningkatkan Aktivitas Dan Hasil Belajar Bahasa Indonesia Materi Masalah, Fakta Dan Opini Sebuah Artikel Menggunakan Model Cooperative Learning Tipe STAD - Lince Sirait (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2021)
This study aims to improve activities and learning outcomes through the application of the STAD type Cooperative Learning model. This study uses classroom action research which has stages of planning, implementation, observation, and reflection, carried out in two cycles, each cycle carried out in two meetings. The research subjects were 36 students. The data needed was obtained through observation, documentation and tests. The validity of the data is done by triangulation technique. The data collected were analyzed using qualitative and quantitative analysis techniques. The results of the study increased learning activities in the initial conditions by 50% or 18 students, the first cycle was 80.56% or 29 students, increased to 94.44% or 34 students, while the student learning outcomes in the initial conditions were 63.06, the first cycle is 74.17, cycle II is 87.50 with learning completeness from 13 students or 36.11% to 58.33%, or 21 students and 88.89% or 32 students in the last cycle.